PENGEMBANGAN JURUSAN PARIWISATA BUDAYA DI PERGURUAN TINGGI HINDU - KETUT SUMADI (Purwadita : Jurnal Agama dan Budaya, 2017)
Tourism  development  is  a  human quality  improvement  effort  undertaken  in  a  sustain able manner, by utilizing the advancement of science and technology and with regard to global developments. Development of cultural tourism in Indonesia with regard art and culture, natu ral  resources  and  local  knowledge.  As  a  basis  for  tourism  development,  then  the  purpose  of tourism development is  to introduce,  utilize, conserve,  and enhance the quality and appeal of travel, maintain norms, religious values, cultural life and natural sound environment, prevent negative influences that can generated by tourism activities, and improve social welfare. In the development of the tourism happens variety of impact or influence on the lives of people around the attractions, so it is necessary that efforts be made to respond, anticipating or responding  to  these  influences,  both  positive  and  negative.  This  effort  is  important  to  do  so tourism can provide benefits, happiness, and prosperity kapada community, nation and state in accordance  with  the  concept  of  development  of  cultural  tourism  in  Indonesia  as  well  as  the tourism world  with the  concept  of  sustainable tourism and community based tourism. One  of them through the development  of tourism science in institutions of  tourism education tourism studies or formal and informal, both at the high school and in college. The problem, whether in Hindu College Tourism Programs can be developed? The problem is discussed in this paper in an effort to  increase  the  participation of  Hindus in  Tourism Development in Indonesia,  while improving the welfare of Hindus through kepariwisataaan.